Prevalence and risk factors for musculoskeletal pain when running during pregnancy: a survey of 3102 women - Wyatt, H. E.; Sheerin, K.; Hume, P. A.; Hébert-Losier, K. (Sports Medicine, 2024)
Background: Musculoskeletal pain while running is a concern to women during pregnancy and can lead to running cessation. To support women who wish to run during pregnancy, it is essential to understand the sites, severities and personal risk factors associated with musculoskeletal pain. Objective: The aim was to investigate prevalence and risk factors for musculoskeletal pain when running during pregnancy. Methods: An online survey was completed by women who had a child in the past 5 years and ran prior to and during pregnancy. Pain frequency informed prevalence rates by body site, and logistic regression odds ratios (ORs) and 95% confidence intervals were calculated. Results: A total of 3102 women of 23 ethnicities from 25 countries completed the survey. Women were 22-52 years old when they gave birth and ran 2-129 km/week during the 0.5-35 years before the birth of their youngest child. Women ran significantly less distance and less often during pregnancy than before pregnancy. Most women (86%) experienced pain while running during pregnancy (59% pelvis/sacroiliac joint, 52% lower back, 51% abdomen, 44% breast, 40% hip). The highest prevalence of severe-to-worst pain was at the pelvis/sacroiliac joint (9%). Women at greatest risk of pain while running during pregnancy had a previous injury (OR = 3.44) or were older (OR = 1.04). Women with a previous child were less likely to experience breast pain (OR = 0.76) than those running during their first pregnancy. Conclusion: Healthcare practices to reduce pain should focus on regions of greatest musculoskeletal change during pregnancy, specifically the pelvis, lower back and abdomen. Efforts to support women to run for longer throughout pregnancy should focus on pain at the pelvis and breasts.